The Correlation Between Infection Diseases History and Nutritional Status in Toddler - Suminar, Ervi; Wibowo, Ach. Riyanto (Universitas Airlangga, 2021)
Introduction: Infection is one of the diseases that often occurs in children under five. Malnutrition is one of the causes of infection. Malnutrition and poor nutrition reduce body resistance to various diseases, especially infectious diseases. The purpose of this study was to determine the relationship between the infectious diseases history and children under five nutritional statuses at Integrated Healthcare Center (Posyandu) Sumur Nangka, Modung District, Bangkalan Regency.Method: This research was observational with cross sectional design. The independent variable is a history of infectious disease and the dependent variable is nutritional status in children under five. The population of this research was all children under five at Posyandu Sumur Nangka, Suwaan Village, Modung Subdistrict, with a total of 45 children with a sample size of 32 children who were selected by simple random sampling. Data collection using a questionnaire. Test data analysis using the Lambda correlation test.Results: The study results showed that 24 (75.0%) children had infectious diseases history and 8 (25.0%) children did not have. Eight (25.0%) children had good nutritional status, 22 (68.8%) children had poor nutritional status, and 2 (6.2%) children had excess nutritional status. Lamda's statistical test showed that the value of p (0.003) <α (0.05) means that H0 is rejected and H1 is accepted. There was a significant relationship between the infectious diseases' history and the nutritional status of children under five.Conclusion: The infection history affects the nutritional status of children under five. Parents must monitor the health of children under five and the nutritional status of toddlers actively by monitoring nutritional intake and weighing toddlers periodically.